Organic carbon and nitrogen mineralization in a poorly‐drained mineral soil under transient waterlogged conditions: an incubation experiment. (5th March 2015) - Tete, E.; Viaud, V.; Walter, C.
<x xml:space="preserve">Abstract</x> Summary In poorly‐drained mineral soils, little interest has been shown on the effects of the duration and frequency of water saturation periods on carbon (C) and nitrogen (N) mineralization. This study investigates C and N mineralization rates in a poorly‐drained mineral soil in response to transient and permanent waterlogged conditions. Soil samples were incubated for 43 days at 20°C under three treatments: field capacity (T0), transient waterlogged conditions (T1) and permanent waterlogged conditions (T2). The carbon dioxide (CO2)‐C and nitrous oxide (N2O)‐N emissions, soil mineral N content (NH4+, NO2− and NO3−) and contents of organic acids were measured. Soil C mineralization rate during transient waterlogged periods (68.7 mg kg−1 after 38 days) was not significantly different to that at field capacity (58.6 mg kg−1 after 38 days) and was twice that of permanently waterlogged soil. In contrast, the N mineralization rate in soil under transient waterlogged conditions was half that of permanently waterlogged soil or soil at field capacity. An accumulation of acetate and formate was measured in the soil during waterlogged periods in treatments T1 and T2; in treatment T1, de‐saturation resulted in a significant decrease in their concentrations. Mineralization of C and N under transient waterlogged conditions was related to aerobic and anaerobic mineralization processes. Rapid mineralization under oxidizing conditions of labile transient organic compounds from anaerobic processes resulted in pulses of CO2‐C and N2O‐N emissions. This study shows that in poorly‐drained mineral soil, C and N mineralization rates at a given time depend not only on the current soil redox status, but also on that of previous soil conditions. Further investigation comparing different durations of waterlogged conditions could allow better understanding of the impact of previous redox conditions on the dynamics of organic acid, C and N mineralization during transient conditions. Résumé Peu d'intérêt a été accordé à l'effet de la durée et de la fréquence des périodes de saturation sur la minéralisation du carbone (C) et de et de l'azote (N) dans les sols minéraux mal drainés. Cette étude a pour but de quantifier la dynamique de minéralisation du C et de N dans un sol minéral mal drainé, en conditions de saturation transitoire et permanente. Des échantillons de sol ont été incubés à 20°C pendant 43 jours selon trois traitements : humidité à la capacité au champ (T0), saturation en eau transitoire (T1), saturation en eau permanente (T2). Les émissions de CO2‐C et de N2O‐N, les concentrations du sol en azote minéral (NH4+, NO2−, NO3−) et en acides organiques ont été mesurées. Une accumulation d'acétate et de formate a été mesurée pendant les périodes de saturation dans les traitements T1 et T2; leur concentration diminue rapidement pendant les périodes de désaturation dans le traitement T1. Nous montrons que le taux de minéralisation du C de T1 pendant les périodes de saturation (68.7 mg kg−1 après 38 jours) n'est pas significativement différent de celui de T0 (58.6 mg kg−1 après 38 jours) et qu'il est deux fois plus élevé que celui de T2. La minéralisation du C et de N dans les sols minéraux mal drainés durant les conditions de saturation transitoire est le résultat des processus de minéralisation aérobies et anaérobies et d'une minéralisation rapide en conditions oxygénées des composés organiques labiles accumulés pendant les périodes de saturation, et conduisant à des pics d'émissions de CO2‐C et de N2O‐N. Cette étude contribue à montrer que, dans les sols minéraux mal drainés, la minéralisation du C et de N à un instant donné ne dépend pas seulement des conditions redox du sol à cet instant, mais aussi des conditions redox qui y ont prévalu. Des travaux complémentaires sur la réponse de la minéralisation du C et N à différentes durées de saturation permettraient de comprendre l'impact des conditions redox antécédentes du sol sur la dynamique de minéralisation des composés organiques en conditions de saturation transitoire.